A Cell-Based Bioelectric Biosensor for Salmonella spp. Detection in Food - Lazaros Konstantinou; Eleni Varda; Stella Pempetsiou; Theofylaktos Apostolou; Konstantinos Loizou; Lazaros Dougiakis; Antonios Inglezakis; Agni Hadjilouka (Engineering Proceedings, 2023)
The prevalence of foodborne diseases is continuously increasing, causing numerous hospitalizations and deaths, as well as money loss in the agri-food sector and food supply chain worldwide. The standard analyses currently used for bacteria detection have significant limitations with the most important being their long procedural time that can be crucial for foodborne outbreaks. In this study, we developed a biosensor system able to perform robust and accurate detection of Salmonella spp. in meat products after a 3-min analysis. To achieve this, we used a portable device developed by EMBIO Diagnostics called B.EL.D (Bio Electric Diagnostics) and a cell-based biosensor technology (BERA). Results indicated that the new method could detect the pathogen within 24 h after a 3-min analysis and discriminate samples with and without Salmonella with high accuracy (86.1%). The method’s sensitivity, specificity, and positive and negative predictive values ranged from 80 to 90.5%, while the limit of detection was determined to be as low as 10 CFU g−1 in all food substrates.